Pengembangan Video Pembimbingan Skripsi Berbasis Self-Learning - Debora Debora; Marko Ayaki Lumbantobing (Jurnal Ilmiah Kanderang Tingang, 2022)
During the Covid-19 pandemic, where social interaction was limited, including in conducting thesis guidance as well as the teaching and learning process in class, face-to-face was replaced with online learning. If the application of learning videos can increase student motivation and achievement, especially undergraduate students, this study will develop a learning video that emphasizes a medium in conducting thesis guidance, namely how to guide thesis to students using video media that will be developed by researchers by emphasizing the guidance provided. also provides experience of scientific thinking processes. The video was developed based on the flow of thought in thesis writing starting from Chapter 1 to Chapter 5, so that the thesis guidance video is a medium in thesis guidance that will facilitate the supervisor in conducting self-learning-based guidance. Students will do self-evaluation, self-improvement and self-strengthening on thesis guidance with a validated thesis guidance video 3 Material Experts and Media Experts with an average score of 74.6% with a decent category. Student responses on material aspects are average. The average score is 3.40 in the good category, the benefit aspect is 3.45 and the benefit is 3.45, all of which are in the good category.